Clinical course of children with postinfectious bronchiolitis obliterans with versus without comorbid bronchopulmonary dysplasia - Lamia Medghoul; Julien Grosjean; Christophe Marguet; Hortense Petat (Clinical and Experimental Pediatrics)
Background Postinfectious bronchiolitis obliterans (PIBO) is a rare chronic obstructive pulmonary disease that occurs after a respiratory infection. Its diagnosis is generally based on clinical history, respiratory symptoms, and computed tomography (CT) findings. Purpose Here we evaluated the frequency of exacerbations, clinical progress, and inhaled corticosteroid (ICS) usage in children diagnosed with PIBO with or without comorbid bronchopulmonary dysplasia (BPD). Methods This retrospective observational study was conducted in Rouen, France. The inclusion criteria were as follows: child diagnosed with PIBO (history of respiratory infection, airway obstruction with no or poor response to bronchodilation treatment, and/or mosaic pattern or trapping on chest high-resolution CT) in 2009–2024 treated with intravenous corticosteroid pulses. Results Fifty-seven patients were included: 13 (23%) with BPD and 44 (77%) without BPD. The mean age at diagnosis was 7.0±3.6 months, with no significant intergroup difference. We observed a significant reduction in exacerbations following corticosteroid pulse treatment as soon as 6 months (P<0.001), with persistent effects observed up to 24 months (P=0.02). We also noted a reduced daily ICS dose starting at 12 months (P=0.03). Respiratory syncytial virus is the most commonly identified causative virus, followed by rhinoviruses and adenoviruses. The viral codetection rates were 18% and 61% in the BPD and non-BPD groups, respectively. Conclusion In our cohort, intravenous corticosteroid pulse treatment effectively treated PIBO, with a rapid and long-lasting reduction in exacerbations and ICS requirements. BPD was a significant comorbidity of PIBO.